Оценка природно-заповедного фонда Западного региона Украины (на примере Ровенской области) - Тарасюк, Ніна Адамівна; Tarasiuk, Nina A.; Ремиз, С. А.; Remiz, S. A. (ТОО «Институт географии» Республики Казахстан, 2015)
Рассмотрены особенности объектов природно-заповедного фонда региона. Проанализирована структура природно-заповедного фонда Ровненской области. Проведена качественная оценка природно-заповедного фонда административных районов области по общим показателям. Рассмотрена зависимость площади природно-заповедного фонда территории от уровня распаханности и лесистости. Обоснованы мероприятия по оптимизации заповедной сети региона.

The regional features of the objects of nature reserve fund have bun considered. The structure of the nature reserve fund of Rovne region has been analysed. It was been made the qualified estimation of administrative districts of the region in condacted on general indexes. The dependence of the square of the Nature Reserve Fund’s territory was been examined according to the level of workability of the soil and development of forest area. The measures of the optimization of the protected zones were justified
The estimation of the nature reserve fund of the western area of Ukraine (on the example of Rovno oblast')
Keywords: индекс инсуляризованности; категории природно-заповедного фонда; коэффициент заповедности; объекты природно-заповедного фонда; природно-заповедный фонд; уровень охранного режима; code insulyaryzovanosti; category of natural reserve fund; reserve ratio; objects of nature reserve fund; Nature Reserve Fund; level protected regime